2023
DOI: 10.1002/biof.1987
|View full text |Cite
|
Sign up to set email alerts
|

Nomilin and its analogue obacunone alleviate NASH and hepatic fibrosis in mice via enhancing antioxidant and anti‐inflammation capacity

Abstract: Nonalcoholic steatohepatitis (NASH) and hepatic fibrosis are leading causes of cirrhosis with rising morbidity and mortality worldwide. Currently, there is no appropriate treatment for NASH and hepatic fibrosis. Many studies have shown that oxidative stress is a main factor inducing NASH. Nomilin (NML) and obacunone (OBA) are limonoid compounds naturally occurring in citrus fruits with various biological properties. However, whether OBA and NML have beneficial effects on NASH remains unclear. Here, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In a CCl 4 -induced liver fibrosis model, obacunone (1.5, 3, and 6 mg/kg) decreased alanine aminotransferase/aspartate aminotransferase (ALT/AST) levels and reversed the pathological changes in the liver tissue, with reduced expression levels of epithelialmesenchymal transition-related proteins (e.g., α-smooth muscle actin and connective tissue growth factor) and lipid oxidation factors and enhanced expression of glutathione peroxi-dase 4 Gene (GPx-4). The administration of obacunone also inhibited pulmonary fibrosis in bleomycin-induced mice [41] and bile-duct ligation-induced cholestatic fibrogenesis mice [42]. Mechanistic studies revealed that the antifibrotic effect was not only related to anti-inflammatory and antioxidant properties of obacunone but also its regulation of the expression and production of GPx-4, the inhibition of TGF-β/SMAD signaling pathway [43,44], and the maintenance of the homeostasis of bile acids.…”
Section: Antifibrosis Effectsmentioning
confidence: 99%
“…In a CCl 4 -induced liver fibrosis model, obacunone (1.5, 3, and 6 mg/kg) decreased alanine aminotransferase/aspartate aminotransferase (ALT/AST) levels and reversed the pathological changes in the liver tissue, with reduced expression levels of epithelialmesenchymal transition-related proteins (e.g., α-smooth muscle actin and connective tissue growth factor) and lipid oxidation factors and enhanced expression of glutathione peroxi-dase 4 Gene (GPx-4). The administration of obacunone also inhibited pulmonary fibrosis in bleomycin-induced mice [41] and bile-duct ligation-induced cholestatic fibrogenesis mice [42]. Mechanistic studies revealed that the antifibrotic effect was not only related to anti-inflammatory and antioxidant properties of obacunone but also its regulation of the expression and production of GPx-4, the inhibition of TGF-β/SMAD signaling pathway [43,44], and the maintenance of the homeostasis of bile acids.…”
Section: Antifibrosis Effectsmentioning
confidence: 99%